PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA DOSEN TETAP PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA ) - irhas irhas (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research aims at finding and the influence of : (1) Emotional  Quotient on  OCB, (2) Spiritual Quotient on OCB, and (3) Organizational Commitment on OCB.  This research is causal associative research which uses questionnaire as the instrument of Data Collection. The Population of this research are 119  Permanent Lecturers  of Private Islamic Higher Education in East Lombok West Nusa Tenggara Indonesia. Questionnaire was used to collect data. The collected data were then analyzed with Linear Multiple Regression.  The result shows that: (1)  Emotional Quotient has positive , but insignificant  effect on  OCB, (2)  Spiritual Quotient has positive and significant effect on  OCB, and (3) Organizational commitment has positive and significant effect  on OCB.Keywords: Organizational Citizenship Behavior, Emotional Quotient, Spiritual Quotient, and Organizational Commitment.